2023
DOI: 10.56215/naia-herald/3.2023.17
|View full text |Cite
|
Sign up to set email alerts
|

Legal regulation of combating organised crime in Ukraine: Сurrent state and areas of improvement

Antonina Vatral

Abstract: The relevance of this study is conditioned by the need to develop concrete proposals for improving the legislation in the field of combating organised crime at the present stage. The purpose of this study was to identify, based on the identified gaps in the legal regulation of combating organised crime, the ways of its improvement with due regard to current socio-political realities and international practices. The study addressed these issues using a system of general scientific and special methods of scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The Russia-Ukraine war combines both conventional and cyber warfare, and this cyber dimension provides an extremely interesting insight into what modern warfare may look like in the future (Guitton & Fréchette, 2023). It is worth noting that organised crime is not the preserve of nonstate actors in international relations but can also include structures within state actors (Vatral, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The Russia-Ukraine war combines both conventional and cyber warfare, and this cyber dimension provides an extremely interesting insight into what modern warfare may look like in the future (Guitton & Fréchette, 2023). It is worth noting that organised crime is not the preserve of nonstate actors in international relations but can also include structures within state actors (Vatral, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Hambali and Z. Zainuddin (2023), considering diversion (diverting) from criminal justice not only as a legal institution but also as a component of the police strategy to combat local crime and to shift the focus from punishing the offender to restoring the state that existed before the offence was committed, concluded that the effectiveness of this legal mechanism by the police was low. At the same time, this statement can hardly be considered a general rule for the institution of diversion (diverting) of children from criminal justice in general, but rather indicates the need to take into account local specifics Vatral, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Hambali and Z. Zainuddin (2023), considering diversion (diverting) from criminal justice not only as a legal institution but also as a component of the police strategy to combat local crime and to shift the focus from punishing the offender to restoring the state that existed before the offence was committed, concluded that the effectiveness of this legal mechanism by the police was low. At the same time, this statement can hardly be considered a general rule for the institution of diversion (diverting) of children from criminal justice in general, but rather indicates the need to take into account local specifics (Shevchuk et al, 2022;Vatral, 2023). Also, relevant is the question of the limits of the use of diversion (diverting) of children from criminal proceedings.…”
Section: Discussionmentioning
confidence: 99%